THE THE ADDITION OF ULTRASOUND AND TAPING ON THE TRANSCUTANEUS NERVES ELECTRICAL STIMULATION (TENS) INTERVENTION REDUCES TENNIS ELBOW PAIN - Asri, Muhammad (Majalah Ilmiah Fisioterapi Indonesia, 2013)
Tennis elbow is one of the muscles around the elbow joint disordersInterventional ultrasound, TENS and taping has been reported to reduce pain.Based on these fenomena established research hypothesis that interventions witha reduction in ultrasound and TENS tennis elbow pain, and there is a relationshipbetween the addition of taping on ultrasound and TENS intervention withreduction in pain of tennis elbow. This experimental study using a randomizedpre test and post test design. Number of samples 28 people who were dividedinto two groups, control group of 14 people, whereas the treatment group asmany as 14 people. This is done starting at the first visit until the sixth visit. Data were analyzed using Paired sample t-test with 95% confidence level. Whereintervention control group (P = 0.03), while the intervention group treated(P=0,01). The conclusions of this study is interventional ultrasound, TENS andtaping is more effective in reducing pain tennis elbow.
Keywords: Pain, ultrasound, electrical transcutaneus nervous stimulant, taping.